Cardiac Autonomic Function and Reactivity Tests in Physically Active Subjects with Moderately Severe COPD. (2nd January 2018) - Mohammed, Jibril; Derom, Eric; De Backer, Tine; De Wandele, Inge; Calders, Patrick
ABSTRACT: Patients with chronic obstructive pulmonary disease (COPD) show impairments in the autonomic nervous systems (ANS) function, which is responsible for cardiac autonomic regulation. This study assessed the autonomic function and cardio-vagal reactivity in conveniently sampled subjects with COPD participating in a pulmonary rehabilitation (PR) program. Twenty-six subjects with COPD and 22 age and gender matched control subjects were evaluated. R-R intervals were collected at rest in supine position. Thereafter, resting autonomic function parameters comprising linear and nonlinear analyses of heart rate variability (HRV) and baroreceptor sensitivity (BRS) were calculated. Autonomic reactivity tests comprising deep breathing (DB), Valsalva maneuver (VM), and head up tilt (HUT) were also performed. The results of this study indicated that resting autonomic function variables were generally reduced in COPD compared to controls. However, this difference was only statistically significant for a few HRV parameters: mean RR intervals, low frequency (LF), standard deviation of dispersion of points perpendicular to the line-of-identity (SD1), and approximate entropy (ApEn) ( p < 0.05). The results also indicated that all cardio-vagal indices following the autonomic reactivity tests were comparable between COPD and controls ( p > 0.05). It was concluded that subtle autonomic impairments exists in physically active COPD patients, and these autonomic function deficits were mainly recognized by resting HRV indices and not autonomic reactivity tests.